Perfecting Sensory Restoration and the Unmet Need for Personalized Medicine in Cochlear Implant Users: A Narrative Review - Archana Podury; Brooke Barry; Karen C. Barrett; Nicole T. Jiam (Brain Sciences)
Hearing loss is one of the most common and undertreated medical conditions worldwide, with an estimated 466 million people (5% of the world’s population) reporting disabling hearing impairment. The implications are significant; untreated hearing loss increases the risk of depression, social isolation, unemployment, cognitive decline, and falls. Cochlear implants (CIs) are surgically implanted electrical devices that allow people with severe hearing loss to process sound. Over the past 50 years, CI development has made remarkable ground, such that most CI users have adequate speech perception in a silent environment. These language achievements, while significant milestones, fall short of perfect sensory restoration. Many of these limitations with complex sound perception are due to our one-size-fits-all approach towards CIs and speech-based metrics for evaluating implant performance. In the past decade, there has been exponential interest in improving CI-mediated music perception, as it serves as a key conduit to restoring normal hearing. The present literature demonstrates the need for a personalized approach towards cochlear implantation and management. Our proposed narrative review illustrates the limitations of CI-mediated sound processing and discusses ways in which precision medicine can be introduced into the ever-expanding hearing loss population.